Treating Progress Functions as a Managerial Opportunity - Dutton, John M.; Thomas, Annie (Academy of Management Review, 1984)
Use of progress functions in strategic planning has led to the principle that firms can expect continuous cost improvements with cumulative output. But finding policies that result in continuous cost improvements requires a better understanding of the dynamics underlying firms' progress functions. This paper draws on more than 200 empirical and theoretical studies of progress functions in industrial engineering, economics, and management. Factors causing progress fall into four categories that vary in origin (exogenous or endogenous) and in type (autonomous or induced).